(untitled) - Jubilee, Sarah (South Africa, 2014)
This book is about the desire of our Bridegroom to prepare His priestly bride because we can only enter the Marriage Supper of the Lamb if we walk according to the order of our High Priest. Our Highest Priest is our bridegroom and therefore we need to be a Priestly Bride. This book is not just filled with words but it is an invitation to a lifestyle of fruitfulness. It contains deep spiritual revelation about who our High Priest is and what he is leading us into.
Keywords: The priestly bride